Demographic features and prognostic factors of uterine carcinosarcoma: a study at a specialized center in Saudi Arabia - Mehros, Wala; Aldosari, Sarah; Alharbi, Rahaf; Alshareef, Wasan; Hawsawi, Wesal; Fallata, Halah; Aljifree, Hatim; Althubaiti, Alaa (Frontiers in Oncology, 2025)
ObjectivesUterine carcinosarcoma is a rare, aggressive biphasic tumor comprising both carcinomatous and sarcomatous elements. The overall prognosis of women with uterine carcinosarcoma is poor, with a median overall survival of less than two years. The predictors of survival for patients with uterine carcinosarcoma in the Kingdom of Saudi Arabia have not yet been fully elucidated; this study therefore explored the demographic features and prognostic factors of uterine carcinosarcoma.MethodsThis A cross-sectional study was conducted among all confirmed carcinosarcoma cases at Princess Noorah Oncology Center, National Guard Hospital, Jeddah, Saudi Arabia, from January 2003 to December 2023. Data were collected on demographic features, medical history, stage, treatment modality, and disease outcome.ResultsA total of 34 patients with carcinosarcoma were identified, accounting for 4.7% of all endometrial cancer cases. Sixty percent of patients were diagnosed early, during stages 2B and below. The most common presentation was post-menopausal bleeding, occurring in 90% of the sample. Kaplan–Meir analysis revealed an overall median survival of 14 months.ConclusionThe findings confirmed the aggressiveness of the tumor. Late tumor stage was identified as a factor affecting patients’ survival and outcome, being associated with poor prognosis and short survival time.